Features of geological structure and prospects of gas content in Zmiiv basement ledge - Suyarko, V. G.; Yakymenko, Ju. V.; Ishenko, L. V. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2015)
Has been reviewed the geological structure and prospects gas content of Zmiiv the basement. It was found that the nature of degree of saturation of hydrocarbons is depends from structure of traps and lithological structure. Zmiiv structure is mostly in Zmiiv district of Kharkiv region. Tectonically it is confined to the northern edge of the Dnieper-Donets basin, which is part of Dnieper-Donetsk avlakogen. Zmiiv basement ledge as a raised unit of the Precambrian basement is a slab, within which no Devonian salt-bearing deposits. Precisely because of this in the sedimentary cover is not enough movably fluid thickness of rock - salt, which could contribute to the oil and gas structure formation. Lateral movement of gas flow and condensate in the direction of raising layers occurred exactly on the places of discontinuous faults. As a result of obstacles such as deep faults and salt rods, transverse directions of migration formed. The main reasons for the migration is compacting of sediments and squeezing forming fluids in thinning areas. Thus, there was saturation of traps by gas and condensate. Sedimentary rocks speech presented terrigenous carbonaceous sediments of the Paleozoic, Mesozoic and Cenozoic, are broken faults of different directions and salt rods. This paved the way for the formation of different origin and form hydrocarbon traps. Among them are dominated tectonic- and lithologic-shielded varieties. Analysis of geological, lithological and tectonic research site features research allowed to define a possible migration route and directions hydrocarbon fluids and place their accumulation in traps not only in the basement rocks Zmiev, but also in the northern part of the near edge zone Dnieper-Donets basin.